Histories of the Future: Utopia and the Politics of Collective Memory in Post-Apocalyptic Fiction - Bussière, Kirsten (Université d'Ottawa / University of Ottawa, 2026)
Over the course of the twentieth and twenty-first centuries, apocalyptic thinking has accelerated rapidly. For many, our position in history is perceived as pre-apocalyptic, resulting in a proliferation of apocalyptic and post-apocalyptic fiction. Though future-oriented, these narratives express an ongoing preoccupation with the function of memory. In fact, the gargantuan corpus of contemporary post-apocalyptic fiction is almost obsessively focused on remembering the pre-apocalyptic past. Moreover, in engaging with contemporary anxieties, post-apocalyptic fiction frequently employs a unique temporal structure that defamiliarizes the real-world present as though it were the fictional pre-apocalyptic past. This thesis is focused on nine popular North American novels: Margaret Atwood's Oryx and Crake (2003), Walter M. Miller's A Canticle for Leibowitz (1959), Russell Hoban's Riddley Walker (1980), Emily St John Mandel's Station Eleven (2014), Peter Heller's The Dog Stars (2012), George R. Stewart's Earth Abides (1951), Octavia E. Butler's Parable of the Sower (1993), Waubgeshig Rice's Moon of the Crusted Snow (2018), and Cherie Dimaline's The Marrow Thieves (2017). These narratives serve as examples of the variety of ways that post-apocalyptic fiction represents both individual and collective memories of the future's past. By reflecting on a defamiliarized version of the real-world present, each text wants us to consider the ways that our current conditions may appear in the future. By interacting with these popular narratives, readers are thus prompted to partake in the imaginary process of remembering and reflecting on fictionalized histories that act as the precursor to the end of the world as we know it. As a result, these texts have the potential to enable readers to reconsider our current living conditions and perhaps propose real-world solutions that mitigate the risks inherent in our present.
Keywords: Post-Apocalyptic Fiction; Apocalyptic Fiction; Dystopian Fiction; Utopian Studies; Memory Studies; Contemporary Literature; Genre Studies; Canadian Literature; American Literature; Indigenous Literature